OBSERVATION OF CONSUMER RESERVATION METHOD SELECTION BY ONLINE TRAVEL AGENT (OTA) - Paulin Tay; Firdaus Yusrizal (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
This research aims to ease, price, trust, and knowledge that given by Online travel agent at Aryaduta Hotel Pekanbaru. Grand Jatra Hotel and Primier Hotel Pekanbaru.This research was used quantitative method toexamined the issues. The sample in this research are 100 people with use Stratified Random Sampling as a method. Meanwhile this research data accumulation technique was used quisnionare, observation, and interviews. Questionnaire measuring technique of this reaseach was used Likert Scale, then the data will processing by quantitative method with numeric result that orientations at clear and certain conclusion. Based on the research that has been done, Online Travel Agent have give ease, low price, trust, and knowledge to their consumer who did make reservation by Online Travel Agent with presentation is over then 60%.Keywords:Online Tavel Agent, Ease, Trust, Price, Knowledge